1988
DOI: 10.1021/jm00400a030
|View full text |Cite
|
Sign up to set email alerts
|

(Acyloxy)benzophenones and (acyloxy)-4-pyrones. A new class of inhibitors of human neutrophil elastase

Abstract: A series of 4-(acyloxy)- and 4,4'-bis(acyloxy)benzophenones were synthesized. Some of them, pivalates (trimethylacetates) and isobutyrates in particular, were found to be potent and selective inhibitors of human neutrophil (leukocyte) elastase. A series of 2-[(acyloxy)methyl]-5-(acyloxy)-4-pyrones were synthesized regioselectively from kojic acid. The 4-pyrones bearing a long chain acyl group at the 2-position and either pivaloyloxy or isobutyryloxy at the 5-position were potent and selective inhibitors of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The title compound was synthesized by amidation of pantothenic acid with 4-aminopivaloyloxybutanol. 4-Aminopivaloyloxybutanol was obtained from N a -Cbz-4-aminobutanol via esterification with trimethylacetylchloride [16], followed by HBr/AcOH deprotection and ether precipitation. Yield: 70%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The title compound was synthesized by amidation of pantothenic acid with 4-aminopivaloyloxybutanol. 4-Aminopivaloyloxybutanol was obtained from N a -Cbz-4-aminobutanol via esterification with trimethylacetylchloride [16], followed by HBr/AcOH deprotection and ether precipitation. Yield: 70%.…”
Section: Methodsmentioning
confidence: 99%
“…Yield: 73%. ES-MS (C16 H 30 N 2 O 5 S, MW 362.49): (ES þ ) 363.1[M + H] þ ; 385.2[M + Na] þ . 1 H NMR (MeOD): 3.88 (1H,s); 3.29-3.50 (4H,m); 3.01-3.05 (4H,m)…”
mentioning
confidence: 99%
“…The derivatives 4-(pivaloyloxy)benzophenone and 4-(isobutyryloxy)benzophenone showed elastase inhibitory activity with half maximal inhibitory concentration (IC 50 ) of 0.62 and 0.25 µM, respectively. It was found that 4,4'-bis(acyloxy)benzophenones were more potent than the corresponding 4-(acyloxy)benzophenones, highlighting 4,4'-bis(2,2-dimethylpropanoate)benzophenone with IC 50 = 0.12 µM and inhibition constant (K i ) = 7.1 × 10 -8 M. 10 Serine proteases are involved in different branches of the immune system and play an important role in inflammation. In a recent investigation from our research group, Martins et al 11 reported in vitro inhibition of serine proteases by synthetic and natural benzophenones, which showed moderate to high inhibitory effects against all the enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have demonstrated that structural modifications carried out on this drug afforded substances with improved anti-inflammatory activity. 9 Miyano et al 10 synthesized a series of 4-(acyloxy)benzophenones and 4,4'-bis(acyloxy) benzophenones and evaluated their anti-inflammatory activity using human neutrophil elastase (HNE) as a template. The derivatives 4-(pivaloyloxy)benzophenone and 4-(isobutyryloxy)benzophenone showed elastase inhibitory activity with half maximal inhibitory concentration (IC 50 ) of 0.62 and 0.25 µM, respectively.…”
mentioning
confidence: 99%
“…The preparation of a reactant to test this plan used known compounds 4 and 5 . Following alkylation of the kojic acid, the THP group can be removed and 6 subjected to pyrolysis (sealed reaction vessel, CEM Discover microwave reactor, IR temperature monitoring).…”
mentioning
confidence: 99%